Thursday

November 27, 2014

November 27, 2014

Posted by **rodrigo** on Friday, December 7, 2007 at 12:47pm.

- college algebra -
**Count Iblis**, Friday, December 7, 2007 at 12:51pmh(-x) = f(-x)g(-x)

f(-x) = -f(x)

g(-x) = -g(x) ---->

f(-x)g(-x) = f(x)g(x) = h(x)

So:

h(-x) = h(x)

- college algebra -
**drwls**, Friday, December 7, 2007 at 12:52pmg(x)*f(x) is an even function, since both f and g change signs when x is replaced by -x

**Answer this Question**

**Related Questions**

Algebra - Let f(x) = 1 – 3x^2. Which of the following is true? Give a brief ...

Calculus, check my answers, please! 3 - Did I get these practice questions right...

odd and even functions - Using f is odd if f(-x) = -f(x) or even if f(-x) = f(x...

Algebra - Confused Please Help! Thanks! Let f(x) = 1 – 3x^2. Which of the ...

Algebra - Let f(x) = 1 – 3x^2. Which of the following is true? Please give us a ...

Algebra - Let f(x) = 1 – 3x^2. Which of the following is true? Give a brief ...

~*~Algebra!*~ - How do you use possible symmetry to determine whether the graph ...

Math - Let f and g be two odd functions. Prove that: a) f + g is an odd function...

algebra - The function f is even and the function g is odd. Determine whether ...

math - I know It's probably an easy question but I don't know remember how to do...